Peningkatan Mutu Pembelajaran Teknologi Pengecatan melalui Metode Jigsaw Bagi Mahasiswa Otomotif FT UNY - Tawardjono Us; Herminarto Sofyan; Gunadi Gunadi (Jurnal Pendidikan Teknologi dan Kejuruan, 2014)
The objective of the study was to investigate (1) the implementation of the jigsaw technique, (2) the students’ participation in the jigsaw technique, and (3) the learning achievement of the students in the course of painting technology through the jigsaw technique. This study used a classroom action research design developed by Kemmis and Mc Taggart in 2 cycles. The study was conducted in the Department of Automotive Engineering Education, Faculty of Engineering, Yogyakarta State University involving 28 students. The data collection method used documentation, observation and tests. The instruments used in this study include: an observation sheet and a written test. The data analysis techniques used comparative descriptive and qualitative. The results of this study were: (1) the implementation of the jigsaw technique was conducted in 2 cycles in the subject of painting defects, with the formation of the groups as heterogeneous, delivering the common materials, a pretest, and group discussions between the source and the expert groups (in 2 cycles), and a post test , (2) learning with jigsaw technique can improve the quality of the students’ learning, and (3) the jigsaw technique increases 74% of the value of the pretest and the post test.